Pengaruh Penggunaan Shopee Paylater Terhadap Pembelian Impulsif Pada Mahasiswa - Fakhira Tri Ismawati A. Saleh; Agus Syam; Muhammad Jufri; Muhammad Rakib; Asmayanti Asmayanti; Andi Reski Nurhikmah; Sudarmi Sudarmi (SEIKO : Journal of Management & Business, 2023)
This study is entitled The Effect of Using Shopee Paylater on Impulsive Purchases for Students of the Faculty of Economics, Makassar State University. The purpose of this study is to determine the effect of using the shopee paylater on the consumptive behavior of students at the Faculty of Economics, Makassar State University. This research is a quantitative research with a descriptive approach. The population in this study were active students of the Faculty of Economics, totaling 4000 students, while the sample in this study was 115 students. Data analysis used is the assumption test, simple linear regression and hypothesis testing. Judging from the results of calculations through SPSS, the coefficient of determination using Shopee Pay has a significant effect on impulsive purchases of 43.8%. While the remaining 56.6% is the influence of other factors not examined in this study. The results obtained are ???? ℎ???????????????????? 0.00 < ???? ???????????????????? 0.05. This shows that ???????? is rejected and ???????? is accepted. Keywords: Use of Shopee Paylater, Impulse Purchases.